Research on the impact of the digital economy on carbon-neutral technology innovation - Geng, Yingying; Li, Chaoyang; Chen, Yiming (Frontiers in Environmental Science, 2025)
At the historical intersection of the “dual carbon” strategy and the digital economy, leveraging digital power to promote environmental governance and technology innovation has emerged as a key area of study. Consequently, investigating how the digital economy influences carbon-neutral technology innovation has become a prominent area of focus. Utilizing panel data from 264 Chinese cities spanning 2011 to 2022, this study explores the influence of the digital economy and its internal structure on carbon-neutral technology innovation. The results show: (1) The digital economy possesses a potent promotional role in driving carbon-neutral technology innovation, and there is regional heterogeneity. (2) Digital industrialization and industrial digitalization, two major systems within the digital economy, have significant promoting impacts on carbon-neutral technology innovation, and compared with industrial digitalization, the promoting effect of digital industrialization is stronger. (3) The digital economy can enhance carbon-neutral technology innovation by improving resource mismatch. (4) When using the digital economy, digital industrialization, and industrial digitalization as threshold variables, the digital economy produces a nonlinear influence on carbon-neutral technology innovation. (5) The digital economy exerts a spatial spillover influence on carbon-neutral technology innovation. The research’s conclusions have certain referential value for promoting China’s digital economy and carbon-neutral technology innovation.